2011
DOI: 10.1002/ibd.21476
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 regulates IL-17A promoter activity and controls RORγt-dependent Th17 colitis in vivo

Abstract: IRF4 can directly bind to the IL-17 promotor and induces mucosal RORγt levels and IL-17 gene expression thereby controlling Th17-dependent colitis. Targeting of this molecular mechanism may lead to novel therapeutic approaches in human IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
63
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 40 publications
3
63
1
Order By: Relevance
“…A recent study concluded that there was no obvious change in IRF1 expression in patients compared with controls. 16 However, another study observed increased expression of IRF1 in 72% of patients with CD among study cohorts. 17 Still, little is known about how IRF1 interacts with multiple cytokines and activates different signaling pathways in the context of IBD.…”
mentioning
confidence: 98%
“…A recent study concluded that there was no obvious change in IRF1 expression in patients compared with controls. 16 However, another study observed increased expression of IRF1 in 72% of patients with CD among study cohorts. 17 Still, little is known about how IRF1 interacts with multiple cytokines and activates different signaling pathways in the context of IBD.…”
mentioning
confidence: 98%
“…Among these are signals downstream of antigen-induced TCR activation that induce expression of the transcription factors IRF4 and Runx1 (14,15). IL-6 activates STAT3, which together with Runx1 and IRF4 promotes ROR␥t transcription (15)(16)(17)(18). TGF␤ signaling through SMAD2 also contributes to Runx1 induction as well as to expression of the ligand-activated transcription factor aryl hydrocarbon receptor (AhR), which is directly implicated in Il17a and Il22 transcription (9,15,19,20).…”
mentioning
confidence: 99%
“…However, recently IB, a nuclear IB family member, was demonstrated to increase IL-17A expression by binding directly to the regulatory region of the IL-17A gene (41). In addition, the transcription factor IFN regulatory factor 4 has been described to directly bind to the IL-17A promoter and thereby regulate the expression of IL-17A (42).…”
mentioning
confidence: 99%